ChemInform Abstract: Stereodivergent Carbamate Synthesis by Selective in situ Trapping of Organic Carbonate Intermediates. Issue 24 (27th May 2016) - Guo, Wusheng; Laserna, Victor; Martin, Eddy; Escudero‐Adan, Eduardo C.; Kleij, Arjan W.
Abstract: Trans carbamates are prepared in a diastereoselective approach by a judicious one‐pot combination of organic carbonates, prepared in situ, and suitable amine reagents under appropriate reaction conditions.